2021
DOI: 10.1016/j.jhep.2021.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of French COVID-19 patients with chronic liver disease: A national retrospective cohort study for 2020

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 28 publications
4
55
0
2
Order By: Relevance
“…Mallet et al have reported the outcomes of hospitalised COVID-19 from the French National Hospital Discharge database including 3207 patients with concomitant cirrhosis. 15 Comparing cirrhotic patients to all noncirrhotic patients produced a mortality OR of 1.73 (1.59-1.88) which is in line with our findings. Adjusted OR for 30-day mortality in compensated cirrhosis (0.71; 0.63-0.80) and decompensated cirrhosis (2.21; 1.94-2.51) were provided, highlighting the importance of delineating cirrhosis severity when prognosticating outcome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mallet et al have reported the outcomes of hospitalised COVID-19 from the French National Hospital Discharge database including 3207 patients with concomitant cirrhosis. 15 Comparing cirrhotic patients to all noncirrhotic patients produced a mortality OR of 1.73 (1.59-1.88) which is in line with our findings. Adjusted OR for 30-day mortality in compensated cirrhosis (0.71; 0.63-0.80) and decompensated cirrhosis (2.21; 1.94-2.51) were provided, highlighting the importance of delineating cirrhosis severity when prognosticating outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Adjusted OR for 30-day mortality in compensated cirrhosis (0.71; 0.63-0.80) and decompensated cirrhosis (2.21; 1.94-2.51) were provided, highlighting the importance of delineating cirrhosis severity when prognosticating outcome. 15 Mendizabal et al have published an update from their prospective study on hospitalised patients with COVID-19, which was already included in this systematic review. 16 This update provided an adjusted OR 3.1 (1.9-4.8) for patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Large registries and data from individual centers suggest that the presence of chronic liver disease (CLD) is associated with poor outcomes, and the risk of mortality is close to 30%-40%. [3][4][5] Among those with CLD, mortality is higher in cirrhotics as compared to non-cirrhotics. [3][4][5] The data available on the influence of COVID-19 in patients with CLD has a few limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Among those with CLD, mortality is higher in cirrhotics as compared to non-cirrhotics. [3][4][5] The data available on the influence of COVID-19 in patients with CLD has a few limitations. First, the data are controversial about the outcome following COVID-19 infection in patients with CLD.…”
Section: Introductionmentioning
confidence: 99%
“…As per our inclusion criteria, all cohort studies were based in Europe and included 23 studies from Spain (14, 16, 17, 22, 28, 29, 32, 33, 35, 50, 54, 57-59, 64, 67, 70, 80, 89, 92, 96, 97, 101), 22 studies from Italy (13,19,21,23,25,30,38,39,45,47,48,55,56,61,62,68,71,77,79,90,91,93), 15 studies from France (20,24,27,31,40,41,43,53,60,63,65,74,76,86,99), ten studies from the UK (26,34,44,49,52,66,72,75,87,98), four included patients from more than one country (69,…”
Section: Resultsmentioning
confidence: 99%